Lithostratigraphy and Biostratigraphy of the Shiranish Formation (Late Campanian- Maastrichtian) in Diana area, Northern Iraq - Al-Dulaimi, Aamer M.; Al-Haj, Mohammed A.; Al-Badrani, Omar A.; Al-Juboury, Ali I. (Iraqi Journal of Science, 2023)
The lithostratigraphic and biostratigraphic studies of the Shiranish Formation in the Diana area, Erbil, Northern Iraq, were conducted to distinguish the main lithostratigraphic units, depositional environment and the formation age. The Shiranish Formation in the study area can be divided into three rock units. The lower and upper units consist of marly limestone, marl and limestone deposited in the outer shelf environment, while the middle unit is dominated by laminated calcareous shale and marl deposited in the upper bathyal environment. Calcareous nannofossils showed the presence of about 20 species/genera in the studied Shiranish Formation. Three biozones are identified; Misceomarginatus pleniporus biozone; Ceratolithoides aculeus biozone, and Uniplanarius sissinghii biozone. From a regional perspective, these biozones were compared with other nannobiozones, leading to the conclusion that the studied section is of Middle Campanian age.